AS CONDIÇÕES NNT E NNR NA REALIZAÇÃO DE UM REFERENCIAL - MONICO, JOÃO FRANCISCO GALERA (Boletim de Ciências Geodésicas, 2005)
Nessa contribuição são apresentados os fundamentos teóricos envolvidos na inserção das condições NNT (No Net Translation) e NNR (No Net-Rotation) na realização de um referencial global. Além disto, são apresentados aspectos concernentes a implementação, com especial destaque para a realização de um referencial advindo de observações VLBI, onde comparece apenas informação de escala. NNT and NNR conditions in the realization of a referential Abstract In this paper the theoretical fundamentals related to the introduction of NNT (No Net Translation) and NNR (No Net-Rotation) conditions in the realization of a referential are presented. Moreover, aspects related to the implementation are also presented, with special emphasis on the realization from VLBI data, where only scale information is available.